Muscle Wasting among Hospitalized Children: A Narrative Review of the Feasibility and Accuracy of Diagnostic Methods - Sheikha AlQahtani; Dara Aldisi (MDPI AG, 2023)
Muscle wasting is associated with a worse quality of life and increased morbidity and mortality among hospitalized children, especially those with chronic diseases. This review was conducted to summarize the data available on the most feasible and accurate diagnostic methods for detecting muscle wasting among hospitalized children, especially to review the evidence of the accuracy and feasibility of conducting assessments using handgrip strength (HGS). Many diagnostic methods are used in hospital settings to assess muscle wasting, by evaluating either muscle mass or strength, with evidentiary support for assessing muscle mass provided using ultrasonography, magnetic resonance imaging, computed tomography, dual-energy X-ray, bioelectrical impedance analysis, and anthropometry measurements. Currently, the most common diagnostic method used to detect muscle strength loss is the handheld dynamometer. Studies support using HGS among healthy and hospitalized children to assess the overall nutritional status and especially muscle function. However, almost all of these studies have been conducted in hospital settings and recruited children with different chronic diseases using a small sample size. More longitudinal cohort studies with large sample sizes are needed to assess the accuracy and feasibility of using HGS among hospitalized children.